Effect of Gene Polymorphisms on Oral Antidiabetic Drug Response in Patients With Type 2 Diabetes Mellitus - Hidayati, Nur Rahmi; Perwitasari, Dyah Aryani; Faridah, Imaniar Noor; Susilo, Rinto (Sciences of Pharmacy, 2025)
Diabetes mellitus is currently one of the global health threats. The prevalence and incidence of this disease continue to increase, both in industrialised and developing countries, including Indonesia. There are different types of DM marker gene polymorphisms in each racial group. These genetic variations contribute to the response of oral antidiabetic drugs. This article aims to conduct a narrative review of the influence of gene polymorphisms on oral antidiabetic drug response in patients with type 2 diabetes mellitus. Article searches were conducted in PubMed, Scopus, Google Scholar, and Wiley published from 2014 to 2024. From the screening, 30 articles met the criteria. The articles reported various gene polymorphisms associated with the efficacy of oral antidiabetic therapy in patients with type 2 diabetes mellitus. In patients with type 2 diabetes mellitus with certain gene variations, there was no significant decrease in HbA1c values after taking medication. Gene polymorphisms may affect the pharmacokinetics of oral antidiabetics and therapeutic response in patients with type 2 diabetes.